An Application of Local Wisdom and Buddhism in Drug Addict Treatment for Social Security in Roi Et Province - Pecharawech, Piyasuda; Sirarat, Patcharee; Phrakruvichitpanyaporn; Russamechay, Siriwudh; Ukot, Arkom (Academic Journal of Mahamakut Buddhist University Roi Et Campus, 2020)
The objectives of the research article were 1) to synthesize the local wisdom in drug addict treatments, 2) to analyze the principles of Buddhist ways in drug addict treatments, 3) to create a formality in applying the local wisdom and Buddhist ways in drug addict treatments, 4) to present the formality of applying the local wisdom and Buddhist ways in drug addict treatments for security in Roi Et province. It is a research method. The research instruments were Questionnaire and interview form. The research results were then analyzed and analyzed for descriptive analysis. The results of the research were as follows: 1.The application of local wisdom in drug addict treatments is an important issue, utilizing things around us. This regards the value of locality. 2.The applying of Buddhist ways in drug addict treatment is a prominent issue. A course about Buddhist Teachings is proposed for those authorities and organizations concerning drug addict treatments, the contents of which should be modern, not boring but attractive for those drug addicts to participate. 3. The patterns of application of folk wisdom and Buddhist ways in the treatment of drug addicts, 1) Applying local wisdom to the treatment of drug addiction, 2) the application of Buddhist ways in the treatment of drug addiction 3.The formality of applying local wisdom and Buddhist ways in drug addict treatments is to formulate a training course with contents on Buddhist Teachings and concrete examples. The speakers of the course must be trained to ensure that those addicts get the right knowledge. The level and intensity of the contents must be suitable for the age range and qualification of the addicts.